1997
DOI: 10.1023/a:1005761031077
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: High grade astrocytomas remain incurable even though these tumors often appear localized on modern imaging studies, rarely metastasize to systemic sites, and can be aggressively treated with surgery and radiation therapy. Recent data suggest that the dissemination of astrocytoma cells along white matter tracts to distant regions of the brain may be responsible for the poor survival of these patients and the limited impact of local therapies. Movement of astrocytoma cells along these white matter tracts can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…Other imaging modalities, such as autoradiography (Geer and Grossman, 1997; Groothuis et al, 1999) and histology may provide higher resolution than what is available with MR; however, they can only be utilized to evaluate final distribution profiles in excised sliced tissue. As mentioned previously, the limited resolution of dynamic MR images (240 µm 2 in-plane) did not allow certain substructures in the hippocampus, such as the granule cell layer of the dentate gyrus or hippocampal fissure, to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Other imaging modalities, such as autoradiography (Geer and Grossman, 1997; Groothuis et al, 1999) and histology may provide higher resolution than what is available with MR; however, they can only be utilized to evaluate final distribution profiles in excised sliced tissue. As mentioned previously, the limited resolution of dynamic MR images (240 µm 2 in-plane) did not allow certain substructures in the hippocampus, such as the granule cell layer of the dentate gyrus or hippocampal fissure, to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion in the ECF compartment may appear anisotropic, due to the hindrances imposed by local differences in tortuosity [155]. White matter tracts are guiding tracts for the interstitial fluid flow as well as for the dissemination of primary brain tumors [158]. Diffusion and exchange between cerebrospinal and extracellular fluid compartments may occur in both directions [37,77] through an uninterrupted single-layered lining of the ventricular system, consisting of several types of ciliated ependymal cells [95,159].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some controversy persists as to the differentiation of multifocal and multicentric disease, perhaps because the described pathophysiological basis for both is similar in some respects. In this report, disseminated disease refers to CSF dissemination, which can result in multicentric disease (Geer et al, 1997) and/or LM. Multicentric disease (and LM) can also occur because of the unique propensity of glioma cells to invade normal brain (or spinal cord) and migrate long distances (Claes et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…By this definition, multifocal glioma consisted of tumors separated by white matter tracts within the same hemisphere, whereas multicentric glioma consisted of widespread tumors, such as those occurring in opposite hemispheres or separated by the tentorium. In contrast to this, Geer and Grossman, in 1997, suggested that interstitial fluid along white matter tracts could be a potentially important mechanism for the dissemination of glioma cells, explaining that glioma cells are inherently capable of migration along white matter tracts to distant areas of the brain (Geer et al, 1997). In 2007, Claes and colleagues (Claes et al, 2007) suggested that multicentric tumors are likely to develop because of the unique propensity of glioma cells to invade normal brain and migrate long distances.…”
Section: Childhoodmentioning
confidence: 99%